Selective serotonin reuptake inhibitors and violent crime: do SSRI’s kill or cure? - S. Sneep; S. Petrykiv (European Psychiatry, 2022)
Introduction SSRI’s are consistently associated with violent events in the adult population. However, the causality between SSRI use and violent behaviour was never found. Several recent studies draw the attention to this hypothesis while they were inspired by several mass murderers in the United States.